Distribution of Human Leishmaniasis (VL) and Its Associated Risk Factors, in Metemma, Ethiopia. (22nd February 2015) - Terefe, Yibeltal; Afera, Berihun; Bsrat, Abrha; Syoum, Zewdu
Abstract : Background . Leishmaniasis is a parasitic disease caused by obligate intracellular protozoans of the genus Leishmania . Objective . To assess the distribution of human leishmaniasis and assess community knowledge, attitude, and practice with regard to assumed risk factors and control options used by the society. Methods . Retrospective study from November 2013 to May 2014 was used. Six-year data from Metemma hospital record was reviewed and 89 people were interviewed. Results . The rates were 29% ( n = 374/1270) and 26% ( n = 328/1270) in 2005 E.C and 2003 E.C, respectively. 94% (1194/1270) of the affected individuals were in the age exceeding 15 years. At the same time, the rates in males and female were 97% ( n = 1226/1270) and 3% ( n = 44/1270), respectively. According to 88.8% ( n = 79/89) of the respondents, transmission occurs through bite of sandflies, while 98.9% ( n = 88/89) of the respondent's indicated that waste disposal in an open space was one of the risk factors for disease occurrence. Regarding the control measures, respondents replied that 73% ( n = 65/89) of them use impregnated bed net and others use cleaning and proper waste disposal. Conclusion . The current finding indicated that the disease was common in the study area; as a result, proper use of impregnated bed net, early diagnosis and treatment, and reduction of different risk factors were essential.